Brown adipose tissue is associated with systemic concentrations of peptides secreted from the gastrointestinal system and involved in appetite regulation. Issue 1 (July 2017) - Chondronikola, Maria; Porter, Craig; Malagaris, Ioannis; Nella, Aikaterini A; Sidossis, Labros S
Abstract : Objective: Brown adipose tissue (BAT) has been proposed as a potential therapeutic target against obesity and its related metabolic conditions. Data from studies in rodents support a cross talk between BAT and other distal tissues. The relation between BAT and peptide hormones secreted from the gastrointestinal system (GI) and involved in appetite regulation is not known in humans. Design: We studied 18 men during thermoneutral conditions and mild non-shivering cold exposure (CE). Methods: 2-Deoxy-2-( 18 F)fluoro-d -glucose positron emission tomography-computed tomography scans were conducted after mild cold to measure BAT volume. Fasting serum concentration of GI-secreted peptides and peptides involved in appetite regulation were measured during thermoneutral conditions and mild CE. Results: During thermoneutral conditions, BAT volume was associated with lower serum concentration of leptin ( P = 0.006), gastric inhibitory polypeptide ( P = 0.016) and glucagon ( P = 0.048) after adjusting for age and body fat percent. CE significantly decreased serum leptin ( P = 0.004) and glucagon concentration ( P = 0.020), while cold-induced BAT activation was significantly associated with lower serum ghrelin concentration ( P = 0.029). Conclusions: BAT is associated with systemic concentrations of GI-secreted peptides and peptides involved in appetite regulation, suggesting a potential cross talk between BAT and the enteropancreatic axis. Further studies are needed to elucidate the potential link of BAT with the postprandial levels of appetite-regulating peptides and the putative role of BAT in appetite regulation in humans.